ANALISIS PENILAIAN KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) PADA PT SUMALINDO LESTARI JAYA Tbk - Makmur Makmur; E. Retno Maninggarjati; Nur Afni Oktabianita (Politeknik Negeri Samarinda, 2020)
The purpose of this study was to determine the financial performance of PT Sumalindo Lestari Jaya Tbk with economic value added method (Economic Value Added) in the period 2015 – 2018. The performance assessment standards is if the EVA is positive then there has been a value added to the company. Conversely, if the value of EVA is negative indivate no value added to the company while the value of EVA = 0 indicate the position of the company is break even. The research method used by the writer is descriptive research by analyzing financial statements using quantitative data that the financial statements of the consolidated financial position and profit or loss of PT Sumalindo Lestari Jaya Tbk listed on the Indonesia Stock Exchange. Data analysis tool used is the method of Economic Value Added (EVA) to calculate the Net Operating Profit After Tax (NOPAT), Weigted Average Cost of Capital (WACC), Total Capital Structure, Capital Charges, and Economic Value Added (EVA). Based on the analysis and discussion conducted at PT Sumalindo Lestari Jaya Tbk during the study period of 2015 -2018 by using EVA, the results show positive EVA in 2015 and 2016, whereas in 2017 and 2018 showed a negative EVA. Keywords: Financial Performance, Economic Value Added (EVA)